2014
DOI: 10.4236/health.2014.616260
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health in University Students from Rio Branco in the Western Brazilian Amazon

Abstract: The objective of this study was to determine the prevalence and associated factors of unsatisfactory self-rated health in university students. A cross-sectional study was conducted in graduate students of a Public University in the city of Rio Branco in the Western Brazilian Amazon. The overall prevalence of unsatisfactory self-rated health was 23.0%. After adjusting for gender and age, the factors associated with unsatisfactory self-rated health were as follows: sedentarism during leisure time (prevalence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
1
2
0
3
Order By: Relevance
“…Psychologically, we speak of health when the student enjoys a set of characteristics such as positive emotions, enthusiasm, vitality, self-determination, and subjective perception of well-being [ 55 , 56 ]. On the other hand, a significant quantity of research indicates the importance of university students’ self-assessed health; when this assessment is unsatisfactory, it is associated with sedentarism, headaches and insomnia and with lower quality of life [ 57 , 58 , 59 ]. In the student population, a low level of well-being has been related to low academic achievement and high levels of procrastination [ 4 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychologically, we speak of health when the student enjoys a set of characteristics such as positive emotions, enthusiasm, vitality, self-determination, and subjective perception of well-being [ 55 , 56 ]. On the other hand, a significant quantity of research indicates the importance of university students’ self-assessed health; when this assessment is unsatisfactory, it is associated with sedentarism, headaches and insomnia and with lower quality of life [ 57 , 58 , 59 ]. In the student population, a low level of well-being has been related to low academic achievement and high levels of procrastination [ 4 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both findings are in line with previously published data. [31][32][33] Tertiles of self-rated health 1st tertile (n=231) 2nd tertile (n=226) 3rd tertile (n=117) P trend* LV hypertrophy, % While the mechanisms for this remain unknown, women may be particularly sensitive to chronic health conditions, thus affecting self-rated health. 34 Recent studies have demonstrated that the prevalence of cardiovascular disease is higher in women, emphasising that an appraisal of sex differences is necessary to obtain maximum benefit of lifestyle interventions for the prevention of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Assim possíveis tendências de maiores prevalências de autoavaliação negativa de saúde com o aumento da idade, conforme observado em pesquisas de base populacional não foram observadas 2,5,25 . Alguns estudos mostram a associação entre hábitos alimentares inadequados e a autoavaliação negativa de saúde 6,26 . No presente estudo, o consumo irregular de verduras/saladas foi associado com a autoavaliação negativa de saúde, o que corrobora com o RP: Razões de Prevalências; IC95%: Intervalo de Confiança a 95%.…”
Section: Discussionunclassified
“…Essa medida de avaliação da saúde é empregada em pesquisas de diversas populações, como em crianças 9 , adolescentes 1-3 , adultos 2,5 , e também em universitários 4,[6][7][8]15 . Para a população brasileira, o sistema de vigilância de saúde, o VIGITEL, para o ano de 2015, mostrou que a autoavaliação negativa de saúde entre os adultos foi de 4,4% 16 , porém, outra pesquisa mostrou prevalência de autoavaliação negativa de saúde de 40% 5 .…”
Section: Percepção Negativa De Saúde Em Universitários Introduçãounclassified
See 1 more Smart Citation